A possible characteristic of foreshocks derived from the evaluation of loading/unloading induced by earth tides - Yu, Huaizhong; Liu, Jie; Ma, Yawei; Yan, Rui; Yu, Chen; Li, Shengle; Yang, Zhigao; Hong, Min; Tu, Hongwei; Zhang, Zhiwei; Zhao, Binbin; Ma, Yuchuan (Frontiers in Earth Science, 2022)
The detection of the potential of a larger event immediately after a moderate earthquake is a quite difficult problem. In this work, we devised an approach to determine whether an earthquake is a foreshock to a larger mainshock by evaluating loading/unloading states. This is done by calculating the Coulomb failure stress (CFS) change induced by Earth tides along the tectonically preferred slip direction on the seismogenic fault surface of each of the candidates. The technique is based on the load/unload response ratio (LURR) method, but the determination of the sliding direction of CFS is different, which is derived from the moderate earthquake that has just occurred rather than the assumption from the regional stress setting. Using the approach, we tested since the year 2000 the Ms ≥ 4.0 foreshocks of the Ms ≥ 6.0 earthquakes on the Chinese mainland, and also the earthquake swarms where no subsequent larger mainshocks were expected in the previous 10 years. The former mostly occurred in the loading process, while the latter arose more frequently in a random process. The marked difference indicates that the occurrence of earthquakes during loading may imply the critical state of the seismogenic faults, and the derived stress is more likely to trigger a larger event than that of the earthquakes that occurred during unloading.